Exploring How the Recruitment System Enhances Employee Performance at Kusuma Agrotourism - Ali Hanafiah; Farah Adiba; C. Evie Dewantara; Fasya Safarah (Goodwood Publishing, 2025)
Purpose: This study explores the impact of recruitment systems on employee performance at PT Kusuma Agrowisata, focusing on how different aspects of recruitment, such as transparency, objectivity, and alignment with organizational goals, influence employee productivity, work attitude, and professional behavior. Research Methodology: Data was collected from 62 employees within the Agrotourism Division of PT Kusuma Agrowisata using a questionnaire that measured recruitment practices and employee performance. The study employed validity and reliability tests to ensure the accuracy of the measurement instrument, followed by data analysis through t-tests and simple linear regression. Results: The study found a significant relationship between recruitment system quality and employee performance, with over 63% of the variation in employee performance explained by recruitment practices. A well-designed recruitment system, which aligns candidate qualifications and organizational needs, significantly improves employee performance. Conclusions: The findings suggest that improving recruitment processes can lead to significant enhancements in employee performance. The study emphasizes the importance of transparent, objective, and well-aligned recruitment strategies as essential tools for organizational success, particularly in specialized industries like agrotourism. Limitations: The study is limited by its sample size of 62 respondents and its focus on the recruitment system alone, excluding other factors such as leadership and organizational culture. Future research could explore the role of these additional factors and use a larger sample to increase generalizability. Contribution: This study provides valuable insights for HR practitioners, especially in the agrotourism sector, on how recruitment practices can be optimized to improve employee performance and reduce turnover. It contributes to the broader literature on human resource management by focusing on niche industries like agrotourism.